A blockchain-enabled security framework for smart agriculture. (March 2023) - Chatterjee, Kakali; Singh, Ashish; Neha,
Abstract: Food consumers are more concerned about transparency, accountability, contamination risks, food safety, and food quality. Thus, an overwhelming demand of a traceability solution is required to address the food consumers' concerns. Blockchain is a promising technique to maintain product traceability in the agricultural food supply chain. The paper proposes a framework which uses the concept of blockchain smart contracts. All the entities engaged in the blockchain-based supply chain network handle the transaction between parties. All transactions are recorded to maintain high transparency and traceability across the supply chain ecosystem. In the event of abuse detection, a group signature mechanism is used. Three metrics, transaction efficiency, system risk reduction, and trust between participants, are considered for testing the system's overall performance. After implementing the framework, the transaction efficiency is measured in terms of gas cost, average execution time, throughput and latency. These parameters show the satisfactory system performance. Graphical abstract: Highlights: A blockchain-based industrial supply chain tracking system is developed to maintain high transparency and traceability. The proposed method also protects data privacy across all parties along with sharing information in a trusted way. A group signature scheme is applied to revoke the signer's identity in case of misuse or dispute. The system's overall performance is evaluated and the results are satisfactory.